(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
The principal focus of this paper revolves around the existential pre-occupation with what it means to be a person. I argue that the work of Jean-Paul Sartre, in particular through the way he placed consciousness centre-stage in his analysis, allows conceptions of the ’self’ that help us, as psychotherapists, in understanding the manifestations of existential anxiety and the possibility of choice in the face of that anxiety. In particular, I consider his analysis of ’Bad Faith’ and the subject/object dichotomy in human relations manifest in his analysis of the ’Look’. A major contribution of his work is the idea that from the maelstrom of consciousness emerges our constant striving for knowledge of who we are and therefore who we might become.